The Influence of Workload on Burnout at PT Pegadaian Cabang Terandam Padang as Mediated by Job Stress - Dini, Rahma; Mia Ayu Gusti (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2026)
Burnout has increasingly emerged as a major concern in today’s workplace, particularly as employees are faced with excessive workloads that may lead to prolonged job-related stress. This condition is especially evident in the context of state-owned financial institutions. Among employees at PT Pegadaian Cabang Terandam Padang indications of burnout caused by workload and job stress were found, which is the primary objective of research. This study used a causal research design and a quantitative approach, with all 60 employees serving as respondents.The method of data analysis selected was Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings that burnout is not much impacted by workload. Workload, however, has been shown to dramatically raise job stress, which has a powerful and substantial impact on burnout. Additionally, the indirect impact of workload on burnout is explained by occupational stress, which acts as a mediating variable. These results indicate that burnout is more likely to arise through stress mechanisms rather than being directly caused by workload alone.